2020
DOI: 10.1371/journal.pcbi.1008407
|View full text |Cite
|
Sign up to set email alerts
|

Tracking collective cell motion by topological data analysis

Abstract: By modifying and calibrating an active vertex model to experiments, we have simulated numerically a confluent cellular monolayer spreading on an empty space and the collision of two monolayers of different cells in an antagonistic migration assay. Cells are subject to inertial forces and to active forces that try to align their velocities with those of neighboring ones. In agreement with experiments in the literature, the spreading test exhibits formation of fingers in the moving interfaces, there appear swirl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Over the past two decades, persistent homology has found many applications in data science, e.g., in the analysis of local behaviour of the space of natural images [7], analysis of images of hepatic lesions [8], human and monkey fibrin [9], fingerprints [10], or diabetic retinopathy images [11], analysis of 3D shapes [12,13], neuronal morphology [14], brain artery trees [15,16], fMRI data [17][18][19], protein binding [20], genomic data [21] orthodontic data [22], coverage in sensor networks [23], plant morphology [24], fluid dynamics [25], dynamical systems describing the movement of biological aggregations [26], cell motion [27], models of biological experiments [28], force networks in granular media [29], structure of amorphous and nanoporous materials [30,31], spatial structure of the locus of afferent neuron terminals in crickets [32], or spread of the Zika virus [33]. An exhaustive collection of applications of topological data analysis to real data can be found at [34].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, persistent homology has found many applications in data science, e.g., in the analysis of local behaviour of the space of natural images [7], analysis of images of hepatic lesions [8], human and monkey fibrin [9], fingerprints [10], or diabetic retinopathy images [11], analysis of 3D shapes [12,13], neuronal morphology [14], brain artery trees [15,16], fMRI data [17][18][19], protein binding [20], genomic data [21] orthodontic data [22], coverage in sensor networks [23], plant morphology [24], fluid dynamics [25], dynamical systems describing the movement of biological aggregations [26], cell motion [27], models of biological experiments [28], force networks in granular media [29], structure of amorphous and nanoporous materials [30,31], spatial structure of the locus of afferent neuron terminals in crickets [32], or spread of the Zika virus [33]. An exhaustive collection of applications of topological data analysis to real data can be found at [34].…”
Section: Introductionmentioning
confidence: 99%
“…We have introduced persistent homology as a novel methodology to the study of spatially extended games. While previous work have used PH to analyze time series of data in other contexts (Bonilla et al, 2020;Pereira and de Mello, 2015;Khasawneh and Munch, 2014), we have demonstrated how it is relevant for understanding spatial notions of evolutionary stability. In Section 2.2, we described three basic shapes that correspond to the stability and instability of strategies in a 2D lattice game (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…It is particularly useful to apply PH to data where connections, holes, and voids play an important role for understanding the studied phenomenon. To that end, PH has been used to detect group alignment and clustering events in biological aggregation models (Topaz et al, 2015), quantify the variability of zebrafish patterns in silico (McGuirl et al, 2020), automatically characterize and compare aspects of collective cell motion (Bonilla et al, 2020), model and quantify protein flexibility (Xia and Wei, 2014), describe atomic configurations in amorphous solids (Hiraoka et al, 2016), and characterize the both clonal and reticulate evolution of RNA viruses (Chan et al, 2013).…”
Section: Tda and Persistent Homologymentioning
confidence: 99%
“…Experiments to quantify the adhesion of the new cells generated by pluripotent stem cells and their ability to stop angiogenesis would be needed. Our passive model of RPE cells could be replaced by a vertex model of the epithelium able to describe wound healing [63]. Including reversible EMT signaling pathways [30] in future models would be desirable and could bring about new therapies.…”
Section: Discussionmentioning
confidence: 99%